miRNA Long-Term Response to Early Metabolic Environmental Challenge in Hypothalamic Arcuate Nucleus - Benoit, Charlotte; Doubi-Kadmiri, Soraya; Benigni, Xavier; Crepin, Delphine; Riffault, Laure; Poizat, Ghislaine; Vacher, Claire-Marie; Taouis, Mohammed; Baroin-Tourancheau, Anne; Amar, Laurence (Frontiers in Molecular Neuroscience, 2018)
Epidemiological reports and studies and rodent models indicate that early exposure to nutrient and/or hormonal challenges can reprogram metabolism at adulthood. Hypothalamic arcuate nucleus (ARC) integrates peripheral and central signals to adequately regulate energy homeostasis. microRNAs (miRNAs) participate in the control of gene expression of large regulatory networks including many signalling pathways involved in epigenetics regulations. Here we have characterized and compared the miRNA population of ARC of adult male rats continuously exposed to a balanced metabolic environment that of adult male rats exposed to an unbalanced high-fat/high-carbohydrate/moderate-protein metabolic environment during the perinatal period and/or at adulthood and, consequently, displayed hyperinsulinemia and/or hyperleptinemia. We identified more than 400 miRNA species in ARC of adult male rats. By comparing the miRNA content of 6 biological replicates in each of the perinatal/adult environments/rat groups, we identified the 10 miRNAs specified by clusters miR-96/182/183, miR-141/200c and miR-200a/200b/429 as miRNAs of systematic and uncommonly high variation of expression. This uncommon variation of expression may underlie high individual differences in aging disease susceptibilities. By comparing the miRNA content of the adult ARC between the four rat groups, we showed that the miRNA population was not affected by the unbalanced adult environment while, in contrast, the expression of 11 miRNAs was repeatedly impacted by the perinatal unbalanced environment. Our data revealed a miRNA response of adult ARC to early metabolic environmental challenge.